Current Strategies for Improvements in the Treatment of Alzheimer’s Disease - Alharbi, Nafaa Fadhel Nafea; Alsabei, Maha Ahmad Seraj; Khayat, Nidaa Abdullah Ibrahim; Alharbi, Malak Salah Nughmush; Alharbi, Abdulaziz Salah Ajab; Al-Harbi, Muhammad Aqa Qablan; alghamdi, Barua Mohammed gamaan; Al-Harbi, Fahad Atqa’a Qablan; Alharbi, Waleed Nafal Awad; Alharbi, Naif Motab Naaqa; et al. (Journal of Posthumanism, 2024)
There have been many promising developments in recent years. Several new targets have been identified and new drugs developed, or existing drugs adapted, to treat AD. However, there are problems with side-effects and specificity. A number of drugs have reduced β-amyloid/ phosphorylated tau levels and improved cognitive function in animal models and in humans but then produced no significant benefit in AD patients in phase 3 trials. Several strategies of treating AD have not been covered here due to lack of space. These include diabetic drugs which are being used to treat AD, metal chaelators, mitochondrial drugs, histamine receptor antagonists and hormone therapy. As our understanding of the links between inflammation, oxidative stress, neuronal damage and the plaques and NFTs found in AD brains improves, new targets may be identified and, perhaps whole new classes of drugs developed. Gene therapy trials are a particularly fascinating development and hold out the hope of restoring lost neuronal function and improving memory, learning and cognition. However, in the short term there is little hope of significant improvement in the quality of life of patients and carers.